Socio-cultural sustainability of pig production: farm visits with citizen panels in the Netherlands and Denmark - Boogaard, Birgit K.; Boekhorst, L.J.S.; Oosting, Simon J.; Sørensen, J.T. (Elsevier, 2011)
Many sustainability studies of animal production consider three pillars: the economic, environmental and socio-cultural. Farmers and animal scientists tend to put most emphasis on the economic and environmental pillar and largely ignore the socio-cultural pillar. Socio-cultural sustainability refers to social perceptions of animal farming, including social appreciations and concerns of animal production systems. Integration of social demands and values in the production sector is a prerequisite to justify animal production within a society. The objective of the present study was therefore to gain further insights into socio-cultural sustainability of pig production. Many citizens may not know what contemporary pig production actually entails. To give people a real life experience with pig production, we conducted farm visits with citizen panels with 18 respondents in the Netherlands and 8 respondents in Denmark. In both countries, respondents were divided over two panels and each panel visited a conventional and an organic pig farm. During the farm visits respondents noted their sensory experiences — what do you smell, hear, see and feel? In addition, each respondent made pictures of six positive and six negative aspects on the farms for which they had to write a motivation. The qualitative analysis resulted in seven socio-cultural themes (SCT) of pig production namely: 1) meat production, 2) farm activities, 3) farm income, 4) animals, 5) housing system, 6) environment and nature, and 7) culture and landscape. Each SCT included several socio-cultural aspects (appreciations, SCA) and socio-cultural issues (concerns, SCI). We identified 31 SCAs in the Netherlands and 33 SCAs in Denmark, of which 29 were SCIs in both countries. Although many issues were associated with animal welfare, the results also showed that social concerns of pig production extended beyond animal welfare. In general it can be stated that citizens are strongly concerned about overexploitation of animals in contemporary pig production systems, but at the same time they appreciate the dynamism in a pig farm including certain modern developments.